2019
DOI: 10.17309/tmfv.2019.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Motor Abilities: Peculiarities of Strength Effort Assessment in Boys Aged 11–13

Abstract: Thepurposeofthestudyistodetermine the peculiarities of strength effort assessmentin boys aged 11-13. Materials and methods.The study participants were boys aged 11 years (n=22), 12 years (n=31), 13 years (n=33). The children and their parents were fully informed about all the features of the study and gave their consent to participate in the experiment. The paper used methods of scientific literature analysis, testing, methods of mathematical statistics. The study assessedthe right hand effort at 1/3, 1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The modes of alternating exercises and rest intervals are considered as a factor that influences the effectiveness of teaching (Burstein et al, 2021;Ivashchenko et al, 2017;Ivashchenko et al, 2015). A dosed load is also used when developing movement control skills (Ivashchenko et al, 2019) and motor abilities Marchenko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The modes of alternating exercises and rest intervals are considered as a factor that influences the effectiveness of teaching (Burstein et al, 2021;Ivashchenko et al, 2017;Ivashchenko et al, 2015). A dosed load is also used when developing movement control skills (Ivashchenko et al, 2019) and motor abilities Marchenko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise with the report from Solomons, Kraak, Kidd & Africa [10], in his research that using RPA on 54 rugby players showed that their biomotors increased significantly. Another study revealed that rhythmic physical activity can be an effective way to improve fundamental movement skills [17], and strength [21]. There had been extensive international research on RPA.…”
Section: Introductionmentioning
confidence: 99%
“…Forming motor skills (Ivashchenko, Berezhna, & Cieślicka, 2020;Khudolii, Iermakov, & Bartik, 2020;Petrov, Khudolii, & Cieślicka, 2020), developing motor abilities (Khudolii, Ivashchenko, Iermakov, Veremeenko, & Lopatiev, 2019;Marchenko & Bezpalko, 2020;Ivashchenko, Mirosława, Nosko, & Malyshev, 2019), and increasing motor activity (Fisher, Reilly, Kelly, Montgomery, Williamson, Paton, & Grant, 2005;Fernández-Valero, Soto-Sánchez, Páez, Leyton-Dinamarca, Kain, Hurtado, & Reyes-Amigo, 2021;Nurulfa, Lubis, Dlis, Aninggar, & Mamesah, 2021) are the main tasks of school physical education and have a positive effect on the health of school students (Vandoni, Codella, Pippi, Pellino, Lovecchio, Marin, Silvestri, Gatti, Magenes, Regalbuto, Fabiano, Zuccotti, & Calcaterra, 2021;Villafaina, Fuentes-García, Leon-Llamas, & Collado-Mateo, 2021;Vlasova, 2020).…”
Section: Introductionmentioning
confidence: 99%